Liquidity creation and bank performance: evidence from MENA - Ahmad Sahyouni; Man Wang (ISRA International Journal of Islamic Finance, 2019)
Purpose: Islamic banks have significantly different balance sheets from their conventional counterparts, leading to different implications in relation to liquidity creation compared to conventional banks. This work, first, investigates the liquidity creation of conventional and Islamic banks in Middle Eastern and North African (MENA) countries between 2011 and 2016. It then tests the relationship between liquidity creation and performance of these banks. Design/methodology/approach - It uses the data of 491 commercial banks across 18 MENA countries between 2011 and 2016. The analysis is based on panel data techniques. Findings - The banks created US18.596 trillion of liquidity, about 28.4% of total assets. Conventional banks created more liquidity compared with Islamic banks. Nevertheless, Islamic banks created more liquidity per asset compared with conventional banks. The regression analysis revealed a significant and negative correlation between liquidity creation and performance of the banks using return on average equity (ROAE) measure. However, no significant relationship is observed between liquidity creation and return on average assets (ROAA) of MENA banks. Moreover, there is no difference between Islamic and conventional banks in the relation between liquidity creation and bank performance. Research limitations/implications - The data are limited to the period 2011-2016; the period of this study was selected based on yearly data availability from the data source. Accounting measures were used to study the effect of liquidity creation on bank profitability, and the market-based measures were excluded, as there is no uniform sources in these countries that can be used to collect market-based data. Practical implications - Bank managers must reach a trade-off between the advantages and disadvantages of liquidity creation, as well as consider the negative relationship between liquidity creation and bank performance whenmaking their decisions. Originality/value - First, to the best of the authors' knowledge, this work is the first to analyse the relationship between the liquidity creation and performance of conventional and Islamic banks in MENA. Second, this study uses a sample of Islamic and conventional banks in MENAthat have detailed information on the Orbis Bank Focus dataset,which is themost comprehensive database of commercial banks in theMENA region.
Keywords: 330; Liquidity creation; Bank performance; ROAA; ROAE; MENA